Pengaruh Media Sosial, Penetapan Harga dan Promosi terhadap Keputusan Pembelian Ulang pada Kedai Kopi Bersahaja - Mohammad Yusuf Hussein; Ustadus Sholihin; Iing Sri Hardiningrum (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to examine the influence of independent variables—Social Media, Pricing, and Promotion—on the dependent variable, Repurchase Decision, at Kedai Kopi Bersahaja. A quantitative research method was employed, utilizing multiple linear regression analysis with the assistance of SPSS 25 software. The population of the study consisted of 226 consumers, and a sample of 107 respondents was selected using incidental sampling techniques. Data were collected through questionnaires distributed to visitors who had made at least one purchase at the coffee shop. The results of the analysis indicate that each independent variable—Social Media, Pricing, and Promotion—has a positive and statistically significant partial influence on the Repurchase Decision. Additionally, the variables collectively demonstrate a strong simultaneous influence, suggesting that an integrated marketing approach is crucial for fostering customer retention and encouraging repeat purchases. Among the three, Social Media showed the most dominant influence, emphasizing the growing role of digital presence and online engagement in shaping consumer preferences and purchasing patterns. Based on these findings, it is recommended that Kedai Kopi Bersahaja maximize the use of social media platforms such as Instagram, TikTok, and Facebook by creating engaging, relevant, and interactive content that resonates with the target audience. Content strategies may include customer testimonials, behind-the-scenes videos, product highlights, and limited-time offers. Pricing should be evaluated periodically to remain affordable yet profitable, considering both market competition and perceived customer value. Meanwhile, promotion efforts can be diversified through the use of loyalty programs, bundle offers, student discounts, and digital coupons. The synergy between these three marketing factors—if consistently and strategically applied—is expected to enhance customer loyalty, strengthen brand image, and significantly increase the likelihood of repurchase decisions. These efforts are essential for building sustainable business growth in the competitive food and beverage industry.